Factors Affecting the Problem of Guidance and Counseling Service Programs in High Schools - Hapsyah, Dina Rahmawati; Herdi, Herdi (Universitas Islam Negeri Raden Intan Lampung, 2019)
The implementation of guidance and counseling services cannot be separated from various factors that can influence. The purpose of this study is to study what factors can affect the implementation of guidance and counseling program services in high school. This study uses descriptive research with survey methods. Data collection techniques used through the instrument contained a questionnaire. The results of the study show that the guidance and counseling program has been well prepared. But the implementation of guidance and counseling is still not good, and this is characterized by high factors that influence the implementation of guidance and counseling service programs. The following are the percentages obtained, among others: personal factors consisting of the competence of the counselor get a percentage of 73% according to the high category; 71% depending on the high category; homeroom teacher obtained a percentage of 79% in the high category; subject teachers earn a percentage of 75%. Non-personal factors consisting of the BK program obtained a percentage of 70 with a high category; Facilities and infrastructure have a percentage of 77% in the high category.